(untitled) (Applied Biological Research, 2013)
Present investigation, conducted on Holstein Friesian crosses maintained at Artificial Breeding Complex, NDRI, Karnal, India, was aimed at to assess the impact of deworming on various semen characteristics of Karan Fries (KF) bulls. Before deworming, no significant (p = 0.122) difference in worm load was observed between control (272.66±6.69 egg g-1) and treated (256.00±5.29 egg g-1) groups. The semen characteristics after deworming were on higher side and significant improvement was noticed only in46.21±5.11 seconds) and osmolality (279.56±2.69 to 292.68±3.04 mOsmol kg-1). Semen volume, mass activity (MA), sperm motility, sperm concentration, non eosinophilic count, pH, total sperm per ejaculate, total motile sperms per ejaculate, total non-eosinophilic count per ejaculate, total non-eosinophilic count mL-1semen and semen dose harvested week-1though on higher side did not show any significant (p>0.05) improvement in KF bulls after deworming. Significant analysis of covariance for MA (p = 0.03) and individual motility indicate that the significant differences may be masked due to pre-treatment effect. Present study showed significant group differences between 3 and 5 weeks after Doramectin application, which almost corresponds to the duration of spermatogenesis in bovines.